Gerakan Lingkar Ganja Nusantara dalam Usaha Mengubah Kebijakan UU No 35 Tahun 2009 Terkait Narkotika Melalui Ruang Publik Masyarakat - Namus Akbar Nasution (Universitas Airlangga, 2023)
This research discusses the Ganja Nusantara Circle social movement in its efforts to legalize marijuana as a medical necessity. This movement was created because of the pros and cons associated with cannabis plants in Indonesia. This study uses the perspective of Jurgen Habermas, which centers on the problem of public sphere. In this case, the purpose of the research related to this movement is more focused on the use of public sphere as the main media in the movement of the LGN. In this paper it was found that cannabis plants also have various benefits, one of which is medical. UU No. 35 of 2009 concerning Narcotics is still not fully relevant in relation to the placement of the cannabis group in narcotics group I. The law also still has several weaknesses, including too many rubber articles, multiple interpretations of articles that sometimes still confuse some parties. The focus in some of the problems related to cannabis plants is that Indonesia still does not have scientific research related to cannabis plants, so this still causes turmoil or differences in perspective for some people regarding marijuana. This research method uses qualitative analysis to explain and describe a phenomenon.